A mathematical model and thermal performance analysis of single-well circulation (SWC) coupled ground source heat pump (GSHP) systems. (25th January 2019) - Tu, Kun; Wu, Qiang; Sun, Haizhou
Highlights: A mathematical model was established to analysis the groundwater seepage. The analytical solution of steady drawdown was derived. The thermal effective radius (TER) of SWC system is much larger that of ground-coupled heat pump (GCHP) systems. It was found that the distribution of temperature field caused by the operation of SWC system is funnel-shaped. Abstract: Owing to the limitation of the available land in China, among various ground source heat pump (GSHP) system configurations, the single-well circulation (SWC) coupled GSHP systems are being intended to provide heating and cooling for building in recent years, especially utilized in this area with suitable hydrogeological and thermogeological conditions. This is due to the fact that the SWC system could not only substantially provide shallow geothermal energy for space heating or cooling in small-scale applications, but also reduce the number of boreholes needed for large-scale geothermal applications. In this work, a mathematical model has been established to analysis the groundwater seepage of SWC system, and analytical solution of steady drawdown was derived. Meanwhile, a numerical model was constructed to evaluate the thermal performance by using SWC coupled GSHP systems. Numerical experiments were performed to observe the evolution of outlet temperature, the distribution of subsurface temperature field, and the long-term development of outlet temperature. It was found that the thermal effective radius (TER) of SWC system is much larger than that of ground-coupled heat pump (GCHP) systems. Also, the temperature field in vertical section caused by the operation of SWC system is funnel-shaped. In addition, the outlet temperature fluctuates annually, and it rather starts a long-term decaying process, until reaching a quasi-steady state after about 8–10 years.